The MRAC based-adaptive control system for controlling the speed of direct current motor - Manh-Cuong Nguyen; Duc-Phuc Vuong; Trong-Thang Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This research aims to propose an adaptive control system for controlling the speed of the direct current (DC) motor. The system consists of two control loops: the first control loop is a traditional PID controller and the second control loop is an adaptive controller. The role of the adaptive controller is adjusting the output of the control object follows with the output of the reference model. The adjustment mechanism is very simple, but the quality of the whole system is very high: the conversion time is short and there isn't overshoot. The quality of the proposed adaptive control system is also compared to the traditional PID control system to show the advantages of the new system.